2009
DOI: 10.1521/aeap.2009.21.3.280
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Analysis of Partner Selection, HIV Serostatus Disclosure, and Sexual Behaviors among HIV-Positive Urban Men

Abstract: Using grounded theory, 18 interviews with HIV-positive urban men were conducted to understand their sexual relationships. Analysis of the verbatim transcripts revealed that regardless of age, sexual orientation or race/ethnicity, the participants were "making choices" related to their sexual relationships. Some men were "avoiding sex" whereas others were engaging in "just sex" or having sex in a relationship that was "going somewhere." However, dependent upon the type of sexual relationship, these HIV-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…Moreover, as in other recent studies in the United States 17 , many participants reported that in addition to "serosorting" (choosing persons with the same serostatus), simply stopping sexual relations with their spouses, or failing to seek new partners, because they found it difficult to cope with the moral imperative of revealing their diagnosis or were not confident that they would be capable of protecting their partners -incapable of hiding what they considered a central aspect of their identity, or of believing that condoms would protect their partners from infection or both from re-infection.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Moreover, as in other recent studies in the United States 17 , many participants reported that in addition to "serosorting" (choosing persons with the same serostatus), simply stopping sexual relations with their spouses, or failing to seek new partners, because they found it difficult to cope with the moral imperative of revealing their diagnosis or were not confident that they would be capable of protecting their partners -incapable of hiding what they considered a central aspect of their identity, or of believing that condoms would protect their partners from infection or both from re-infection.…”
Section: Discussionsupporting
confidence: 75%
“…Meanwhile, many male and female partners, even when they were HIV-negative and aware of the partner's diagnosis, accepted or even proposed having sex without condoms, because "love is blind" as one bisexual man reported, or because "sometimes [the woman] seems silly, pretending I don't have [HIV]". As observed in other studies with men 16,17 , sexual activity in the context of conjugality or a relationship involved different practices as compared to those in the context of relations with lovers or affairs (regular but not conjugal partners), further differing from practices with partners paid for "programa" (exchanged for money or favors), with repercussions on the disclosure process. Again, one observes that unprotected sex occurs more frequently with other persons also living with HIV as compared to sex with partners of unknown serostatus or whom one knows to be HIV-negative 17,18 .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…5 Disclosure can promote other strategies that PLHIV, and men who have sex with men (MSM) living with HIV in particular, use to engage in safer sex behaviors, such as facilitating pre-exposure prophylaxis 6 and serosorting. 7 Because of the potential for HIV disclosure to improve sexual communication and health, it is important to understand what factors, such as depression, affect disclosure early in the course of living with HIV.…”
mentioning
confidence: 99%
“…Studies have produced intriguing findings about the interactions of disclosure to family, social support, and immune function (Fekete et al, 2009). However, disclosure may also be a source of stress, particularly if it results in negative consequences or involves revealing potentially stigmatized behaviors, such as homosexuality (Relf et al, 2009). Individuals who report feeling shame or stigma related to their HIV serostatus are less likely to disclose (Derlega et al, 2002), especially to casual partners (Serovich & Mosack, 2003).…”
Section: Literature On Disclosurementioning
confidence: 99%